The evolution of resource property rights - Scott, Anthony, 1923- (Oxford : Oxford University Press, 2008)
Individuals' rights to use natural resources have long existed. This title traces the development of these rights and looks at how individuals' rights have evolved. Each chapter focuses on a single natural resource property right, noting the impact of technology, the role of the common law courts, and the role of government.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Natural resources; Right of property -- History; Natural resources, Communal; Natural resources -- Co-management.